2011
DOI: 10.2460/javma.238.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Sickness behaviors in response to unusual external events in healthy cats and cats with feline interstitial cystitis

Abstract: Objective To compare sickness behaviors (SB) in response to unusual external events (UEE) in healthy cats with those of cats with feline interstitial cystitis (FIC). Design Prospective observational study. Animals 12 healthy cats and 20 donated cats with FIC. Procedures Cats were housed in a vivarium. Sickness behaviors referable to the gastrointestinal and urinary tracts, the skin, and behavior problems were recorded by a single observer for 77 weeks. Instances of UEE (eg, changes in caretakers, vivariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 27 publications
4
124
2
3
Order By: Relevance
“…There have been suggestions that early life experiences may be involved in modifying stress responses and manifestations of disease (Buffington 2009), and it has also been suggested that FIC may be one of a number of stress-related disease manifestations seen in some cats that include gastrointestinal, respiratory, dermatological and behavioural signs (Buffington 2004, 2011 Buffington and others 2006a, 2006b). However, further work is needed to investigate these hypotheses and, interestingly, in a study that deliberately exposed cats with long-standing recurrent FIC to stressful stimuli no signs of FIC recurring were observed (Stella and others 2011). …”
Section: Pathogenesis Of Feline Idiopathic Cystitismentioning
confidence: 99%
“…There have been suggestions that early life experiences may be involved in modifying stress responses and manifestations of disease (Buffington 2009), and it has also been suggested that FIC may be one of a number of stress-related disease manifestations seen in some cats that include gastrointestinal, respiratory, dermatological and behavioural signs (Buffington 2004, 2011 Buffington and others 2006a, 2006b). However, further work is needed to investigate these hypotheses and, interestingly, in a study that deliberately exposed cats with long-standing recurrent FIC to stressful stimuli no signs of FIC recurring were observed (Stella and others 2011). …”
Section: Pathogenesis Of Feline Idiopathic Cystitismentioning
confidence: 99%
“…32,33 Cats faced with unexpected changes to their management may decrease appetite and water intake, avoid elimination for 24 hours (potentially increasing the risk of constipation), and defecate outside the litter tray. 34 In general, food intake and stress seem to be negatively correlated in cats, 28 whereas in dogs, associations have been made between increased stress and coprophagia 35 and inflammatory bowel disease. 36 The Integument…”
Section: Reproductive Systemmentioning
confidence: 99%
“…With regards to the exploratory analyses, the risks of biting, lack of adoption, and euthanasia could potentially be mitigated by interventions designed to decrease stress in the shelter environment, such as minimizing loud noises and intrinsically unpleasant conditions, consistency with human caretakers, consistency with diet, and hiding and perching areas (Carlstead et al, 1993;Stella, Lord, & Buffington, 2011;Vinke, Godijn, & van der Leij, 2014).…”
Section: Discussionmentioning
confidence: 99%